An Initial Verdict on Our Fight Against Poverty - Celia M. Reyes (Philippine Institute for Development Studies (PIDS), 2004)
The primary objective for the conduct of the assessment of the social sector is to provide the basis for setting the thematic priorities for the Philippines, taking into account the development requirements in the next five years. The specific objectives of the study are: (i) to review the major accomplishments during the period 1989 -2003 in the social area, taking into account the targets set by the government, if any, during this time; (ii) to identify the critical factors which contributed to the attainment of the major accomplishment in the social areas during the period; (iii) to identify areas where accomplishments were lagging behind targets and the problems encountered that led to poor performance in these areas; and (iv) to propose an action plan in the social area for the period 2004-2008, composed of key strategic interventions where maximum impact can be achieved. The assessment covers 4 administrations, Aquino (1986-1992), Ramos (1992-1998), Estrada (1998-2001) and Macapagal-Arroyo (2001-present). It draws upon secondary data and earlier assessments done. The social developments in the Philippines are viewed from the overall context of poverty as the major development problem of the country. The concept of poverty as being multidimensional is adopted in this study. Consequently, various indicators relating to the different dimensions of poverty are used to gauge the performance of the country. The Philippines performance with regards to reducing the different dimensions of poverty has been generally modest and mixed. While the country has achieved notable gains in several non-income based measures of poverty, the performance with regards to income-based measure of poverty has been unremarkable. This paper also proposes an action plan for the social sector that identifies key strategic interventions for the next five years.
Keywords: 330; targeting; poverty; decentralization; chronic poverty; transient poverty; community-based monitoring system; Armut; Armutsbekämpfung; Dezentralisierung; Sozialpolitik; Entwicklung; Philippinen